2021
DOI: 10.1016/j.neo.2021.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous hydrogen sulfide regulates xCT stability through persulfidation of OTUB1 at cysteine 91 in colon cancer cells

Abstract: Increased xCT and transsulfuration pathway has been associated with metabolic reprogramming of colorectal cancer. However, the correlation between these 2 events and the underlying molecular mechanism remains obscure. xCT expression was determined in tissue microarrays of colorectal cancer. RNA sequencing and functional assays in vitro was adopted to delineate the involvement of transsulfuration pathway in the proper function of xCT in maintaining the chemoresistant phenotype. The synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 44 publications
1
25
0
Order By: Relevance
“…H 2 S has an antioxidative effect by increasing GSH content and reducing ROS [ 215 ]. In addition, to reduce ferroptosis, GPX4 activity is inhibited while the Xc system is kept stable [ 216 , 217 ]. GSH depletion is an essential feature of ferroptosis.…”
Section: H 2 S and Ferroptosismentioning
confidence: 99%
See 1 more Smart Citation
“…H 2 S has an antioxidative effect by increasing GSH content and reducing ROS [ 215 ]. In addition, to reduce ferroptosis, GPX4 activity is inhibited while the Xc system is kept stable [ 216 , 217 ]. GSH depletion is an essential feature of ferroptosis.…”
Section: H 2 S and Ferroptosismentioning
confidence: 99%
“…The beneficial effects of H 2 S on ferroptosis suppression have recently been demonstrated in research. H 2 S inhibits ferroptosis by suppressing ALOX12 acetylation and controlling the stability of the xCT (the functional submit of the Xc system), according to Wang and Chen et al [ 216 , 222 ]. Therapy with the H 2 S donor GYY4137 reduces ferroptosis, which helps to reduce acute lung damage [ 223 ].…”
Section: H 2 S and Ferroptosismentioning
confidence: 99%
“…Rather than depending on its deubiquitination ability, OTUB1 stabilizes SLC7A11 by inhibiting the E2-conjugating enzymes recruited by E3 ligases 140 . Accumulating evidence has shown that depletion of OTUB1 sensitizes multiple tumor cells to ferrotopsis, including glioma 141 , colon cancer 142 , breast cancer 143 , and pancreatic cancer 144 , thereby modulating OTUB1 might be a promising strategy for cancer therapy. Palladium pyrithione complex (PdPT) is a pan-inhibitor of multiple DUBs, including USP7, USP10, USP14, USP15, USP25, and UCHL5, which contributes to ferroptosis and apoptosis in NSCLC cell lines.…”
Section: Ferroptosis Regulated By Dubsmentioning
confidence: 99%
“…Mutual regulation between xCT and H2S can be suppressed by AOAA and Erastin. This combined therapy leads to ferroptosis in chemoresistance colon cancer cells [ 73 ]. It is well known that many saponins are anti-tumor drugs.…”
Section: Ferroptosis and Colon Cancermentioning
confidence: 99%